2022
DOI: 10.1021/acs.langmuir.1c02724
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Polymer-Surface Adhesion with a Polymer Collection

Abstract: Polymer modification plays an important role in the construction of devices, but the lack of fundamental understanding on polymer-surface adhesion limits the development of miniaturized devices. In this work, a thermoplastic polymer collection was established using the combinatorial laser-induced forward transfer technique as a research platform, to assess the adhesion of polymers to substrates of different wettability. Furthermore, it also revealed the influence of adhesion on dewetting phenomena during the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, the same transfer parameters (89 mW laser power, 4000 dpi resolution, laser on time 400 µs per dot) were used for all substrates and no pre‐treatments of the acceptor surfaces were performed. We selected commercially available PS due to its favorable properties, such as outstanding LIFT processability (largest material amounts transferred in our approach), [ 33 ] suitable hydrophobicity, glass transition temperature, low‐cost, and widespread use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the same transfer parameters (89 mW laser power, 4000 dpi resolution, laser on time 400 µs per dot) were used for all substrates and no pre‐treatments of the acceptor surfaces were performed. We selected commercially available PS due to its favorable properties, such as outstanding LIFT processability (largest material amounts transferred in our approach), [ 33 ] suitable hydrophobicity, glass transition temperature, low‐cost, and widespread use.…”
Section: Resultsmentioning
confidence: 99%
“…Future studies will also address the minimization of the delay time between the transfers of two spots, as well as further explore additional polymers for high‐resolution labels. We have previously shown that for example also polylactic acid, various copolymers, polyvinyl chloride, [ 33 ] or poly(dimethylacrylamide), [ 39 ] can be compatible with our process. A low‐cost version of the laser setup can enable this process in any lab.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…During the CVD process, the state of the polymer matrix gradually changes as temperature increases. It becomes viscous above the glass transition temperature of 67.2 °C 39 , allowing diffusion similar to a solvent layer 40 , 41 , followed by its decomposition at about 400 °C (Fig. S 5 ), and the formation of a carbon skeleton (compare Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stimuli-responsive polymers have wide-ranging applications in various fields such as optics, , electronics, thermodynamics, mechanical systems, etc ., and have thus garnered significant attention from researchers. , Specific applications of these polymers include biosensing, adaptive surface adhesion, self-healing, drug delivery, etc . In the field of biology and medicine, biologically responsive materials play an important role in detecting and amplifying pathophysiological signals to aid early identification of diseases .…”
Section: Cancer Diagnosis Via Molecular Imagingmentioning
confidence: 99%